Pet exposure in utero and postnatal decreases the effects of air pollutants on hypertension in children: A large population based cohort study. (July 2018) - Lawrence, Wayne R.; Yang, Mo; Lin, Shao; Wang, Si-Quan; Liu, Yimin; Ma, Huimin; Chen, Duo-Hong; Yang, Bo-Yi; Zeng, Xiao-Wen; Hu, Li-Wen; Dong, Guang-Hui
Abstract: The effect of ambient air pollution exposure on childhood hypertension has emerged as a concern in China, and previous studies suggested pet ownership is associated with lower blood pressure (BP). However, limited information exists on the interactive effects pet ownership and air pollution exposure has on hypertension. We investigated the interactions between exposure to pet ownership and air pollutants on hypertension in Chinese children. 9354 students in twenty-four elementary and middle schools (aged 5–17 years) in Northeastern China were evaluated during 2012–2013. Four-year average concentrations of particulate matter with aerodynamic diameter of ≤10 μm (PM10 ), SO2, NO2, and O3, were collected in the 24 districts from 2009 to 2012. Hypertension was defined as average diastolic or systolic BP (three time measurements) in the 95th percentile or higher based on height, age, and sex. To examine effects, two-level regression analysis was used, controlling covariates. Consistent interactions between exposure to pet and air pollutants were observed. Compared to children exposed to pet, those not exposed exhibited consistently stronger effects of air pollution. The highest odds ratios (ORs) per 30.6 μg/m 3 increase in PM10 were 1.79 (95%confidence interval [95%CI]: 1.29–2.50) in children without current pet exposure compared to 1.24 (95%CI: 0.85–1.82) in children with current pet exposure. As for BP, only O3 had an interaction for all exposure to pet ownership types, and showed lower BP in children exposed to pet. The increases in mean diastolic BP per 46.3 μg/m 3 increase in O3 were 0.60 mmHg (95%CI: 0.21, 0.48) in children without pet exposure in utero compared with 0.34 mmHg (95%CI: 0.21, 0.48) in their counterparts. When stratified by age, pet exposure was more protective among younger children. In conclusion, in this large population-based cohort, pet ownership is associated with smaller associations between air pollution and hypertension in children, suggesting pet ownership reduces susceptibility to the health effects of pollutants. Graphical abstract: Image 1 Highlights: Long-term exposure to air pollution may elevate odds of hypertension in children. Pet ownership modifies the association between air pollution and hypertension. Early childhood pet exposure may buffer the effect of air pollution on hypertension. Abstract : Pet ownership in early childhood may buffer the adverse effects of air pollution exposure on hypertension.